FOREIGN LANGUAGE BEHAVIOR OF ISLAMIC BOARDING SCHOOL STUDENTS IN WEST SULAWESI - Ahmad Muaffaq; Napis Dj (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
Students of Islamic Boarding Schools in West Sulawesi come from various ethnicities. They relatively concern about their pride, loyalty, and awareness of foreign language norms as an essential part of the Islamic Boarding School curriculum. It also has an impact on the quality of its acquisition. This study aims to describe the students' behavioral patterns in using foreign languages and their factors. The data was excavated from informants on five Islamic Boarding Schools integrated with stratified random sampling models. Data collection techniques were observations, surveys, and interviews. The obtained data were carefully and critically analyzed based on data reduction, presentation, and verification methods. The results showed that the foreign languages in Islamic Boarding Schools at West Sulawesi are generally used passively because the students’ activities highly focus on improving students’ ability in reading. The emphasis is also on the ability to understand Arabic text. Regarding Islamic Boarding School that applies language development for reading and active communication, sociologically, students use foreign languages only in a small number of linguistic situations and in specific domains, namely education. Culturally, foreign language behavior breeds symptoms of multilingualism, bilingualism, code-switching and code-mixing, monolingualism, and interference in all linguistic situations. It is due to the responsibility, loyalty, and motivation of foreign affairs that are still lacking and the insufficient quality of teachers, environmental conditions, and curriculum content.